Modern Nucleophilic Aromatic Substitution. By Francois Terrier. Issue 28 (20th May 2014) - Mayr, Herbert
<x xml:space="preserve">Abstract</x> Wiley‐VCH, Weinheim, 2013. 488 pp., hardcover, € 150.00.—ISBN 978‐3527318612<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>